Analysis of the Role of Android-Based Learning Media in Learning Critical Thinking Skills and Scientific Attitude - Isnaeni, W.; Sujatmiko, Y. A.; Pujiasih, P. (Jurnal Pendidikan IPA Indonesia, 2021)
This study aims to analyze and describe android-based learning media's role in teaching students critical thinking skills and scientific attitudes. The learning media are Androwebic (android-based webcomic) and E-Bokartumban (e-book on plant diversity in Banjarnegara), developed previously. This research is a qualitative descriptive study involving 301 students, six biology teachers and six high school students. The data collected includes critical thinking skills, analytical skills, scientific attitudes, environmental care attitudes, media components supporting student competence, and teacher and student responses. Data on critical thinking and analytical skills were measured using tests and non-tests. Other data were measured using non-test instruments, including interview guides, scientific attitude observation sheets, students' environmental care attitudes, media component observation sheets, and student and teacher questionnaires. Quantitative data on critical thinking and analytical skills were analyzed using the n-gain test, while other data were descriptively analyzed. The research results showed that the E-Bokartumban and Androwebic components support students' critical thinking skills, analytical skills, and environmental care attitudes. Androwebic can train students' analytical thinking skills and scientific attitude. The two media developed were considered very helpful in the learning process. The study concluded that Android-based media in Androwebic and E-Bokartumban have a vital role in training critical thinking skills, analytical skills, scientific attitudes, and environmental care attitudes.